A facile and green route to terpene derived acrylate and methacrylate monomers and simple free radical polymerisation to yield new renewable polymers and coatings. Issue 16 (6th April 2016) - Sainz, M. F.; Souto, J. A.; Regentova, D.; Johansson, M. K. G.; Timhagen, S. T.; Irvine, D. J.; Buijsen, P.; Koning, C. E.; Stockman, R. A.; Howdle, S. M.
Abstract : We present new acrylic monomers, polymers and coatings derived directly from abundant naturally available terpenes via facile, green and catalytic approaches. Abstract : We present new acrylic monomers derived directly from abundant naturally available terpenes via a facile, green and catalytic approach. These monomers can be polymerised to create new polymers with a wide range of mechanical properties that positions them ideally for application across the commodity and specialty plastics landscape; from packaging, cosmetic and medical, through to composites and coatings. We demonstrate their utility through formation of novel renewable polymer coatings.